Kualitas Tepung Ikan di Pesisir Pantai Kabupaten Merauke Sebagai Bahan Pakan: Quality of Fish Flour on the Coast of Merauke Regency as Feed - Irine Ike Praptiwi; Wahida Wahida (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Catch fish that are not used as food can be processed into fish flour. The purpose of this study was to analyze fish meal from several types of fish found on the coast of Merauke RegencyThis test is carried out to see the physical and chemical quality.. From the research results of this study obtained the physical quality of fish meal can be which is categorized, both in mixing feed food and storage namely: the average density of 0.58 gr / cm3, surface area 53.88 cm2, pH 6.25, threshold power 1.15 m / sec and stack angle 27.260C, average ash content of 6.31%, protein 65.46%, fat 5.46%, crude fiber 0 and water content an average of 6.32%, These results indicate the quality of fish meal is included in standard I based on the quality of SNI 2013 as feed material. Eight (8) types of fish meal that have low economic value and potential to be developed as feed ingredients include Kaca fish (Kurtus gulliveri, Pasir fish (Platycephalus endrachtensis), Bete-Bete fish (Rhinoprenes pentanemus), Duri Herkules fish (Arius sp), and Duri putih fish (Arius leptaspis).